Attribution and the Illegality Defence. Issue 3 (May 2016) - Lim, Ernest
Abstract : In Jetivia SA v Bilta (UK) Ltd (in liquidation) all seven judges of the Supreme Court affirmed the decision of the Court of Appeal by holding that the illegality defence could not be raised as a defence against the claim made by the company because the wrongdoing of the directors and shareholder cannot be attributed to the company. Although all the judges unanimously agreed on the outcome of the case, their reasoning concerning the approach to attribution and the different circumstances under which attribution should or should not take place differed. Further, the Supreme Court was divided on the issue of the correct approach to the illegality defence.